A multi-syringe flow injection system for the spectrophotometric determination of trace levels of iron in waters using a liquid waveguide capillary cell and different chelating resins and reaction chemistries - Páscoa, Ricardo N. M. J. (2010)
A method integrating a long waveguide capillary cell with a preconcentration resin in a multi-syringe flow injection analysis (MSFIA) system for iron determination in waters was developed. The determination of iron is based on a colorimetric reaction and two reagents were tested, ferrozine and ammonium thiocyanate. A liquid waveguide capillary cell (1.0 m pathlength, 550 μm i.d. and 250 μL internal volume) with a preconcentration resin were used to improve the sensitivity of the determination. Two different preconcentration resins were also tested, Chelex 100 and NTA Superflow. The developed method employing the NTA Superflow with ferrozine colorimetric reagent provided a detection limit of 0.05 μg L−1 with a linear response up to 8 μg L−1 and a sample throughput rate of 12 per hour. The developed system presents low reagents/sample consumptions. The accuracy was assessed using a certified reference water sample.